Анализ влияния способа соединения столбиковых выводов интегральных схем на их сопротивление - Hotra, Z. Yu.; Dyachok, D. T. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
A model of a rigid pillar lead between the contact pads of the IC substrate and the mounted chip is considered. A method for determining the electrical resistance of the lead is proposed, and the resistance of the pillar lead for different connection methods is determined using this method. The results of the work are recommended for use in the design of semiconductor devices and integrated circuits with pillar (ball) leads.